Intellectual property box regimes: Effective tax rates and tax policy considerations - Lisa Evers; Helen Miller; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
11 European countries now operate IP Box regimes that provide substantially reduced rates of corporate tax for income derived from important forms of intellectual property. We incorporate these policies into forward-looking measures of the cost of capital, effective marginal tax rates and effective average tax rates. We show that the treatment of expenses relating to IP income is particularly important in determining the effective tax burden. A key finding is that regimes that allow expenses to be deducted at the ordinary corporate income tax rate, as opposed to the IP Box tax rate, may result in negative tax rates and can thereby provide a subsidy to unprofitable projects. We assess the specific design features of different regimes against the possible policy aim of improving the incentives to undertake R&D investment in a country. While some countries have tried to tie the policy to real activities, others have designed a policy targeted at the income streams associated with intellectual property. A key concern is the role that IP Boxes may play in increased, and possibly harmful, tax competition between European countries.
urn:nbn:de:bsz:180-madoc-347712
Keywords: H25; H32; H87; K34; O38; 330; corporate taxation; effective tax rate; innovation; tax incentive patent box; innovation box; license box; tax competition